PENDAMPINGAN PENGAWALAN BLT-DD TERKAIT KEBIJAKAN PERMENDESA NOMOR 6 TAHUN 2020 DI KECAMATAN GALANG KABUPATEN TOLITOLI - Fitriyah Astri; Hasanuddin Hi Pende (ABDI KAMI: Jurnal Pengabdian Kepada Masyarakat, 2020)
The article is intended to escort assistance related to social safety nets of the vilage fund on the urban policy. Facts in that field the translation of regulations related to social safety nets still differns between policy markets, therefor assistance is urgently needed by the village government. The method used is socialization, on job trainning, discussion, feedback and monitoring. As for the results of the resulting activities, all stages are carried out, starting form the census of the poor by the hamlet head, deliberations to distribution according to the mechanism. Furthermore, assistance to village administrators or village institutions related to the planning and implementation process can run according to the applicable mechanisms and regulations.